PREVENTION OF CORRUPTION BEHAVIOR IN SD CHILDREN THROUGH 7 POE ATIKAN CHARACTER EDUCATION: QUALITATIVE STUDY - Pratama, Deri Fadly; Kelana, Jajang Bayu; Rahayu, Galih Dani Septian (PrimaryEdu : Journal of Primary Education, 2021)
This research was conducted in general with the aim of analyzing the 7 poe atikan of character education in elementary schools (SD) in an effort to prevent corrupt behavior in elementary school children. The specific purpose of this study was to find out all students who know about corruption in elementary school age children and to know the impact of character education on corrupt behavior among elementary school students. This research was conducted using a qualitative descriptive method with instruments used in the form of questionnaires and interviews. The subjects in this study were 30 students of grade V SDN 8 Ciseureuh Kahuripan Pajajaran. The results of this study indicate that grade V students have seen several activities in daily life including positive and negative attitudes related to corrupt behavior and character education which have a positive impact on students 'understanding related to students' understanding of corrupt behavior and methods. avoid the behavior. The conclusion from this research is that 7 points of character education can have a positive impact in preventing corrupt behavior among elementary school students.